Richness and distribution of endangered orchid species under different climate scenarios on the Qinghai-Tibetan Plateau - Hu, Huawei; Wei, Yanqiang; Wang, Wenying; Suonan, Ji; Wang, Shixiong; Chen, Zhe; Guan, Jinhong; Deng, Yanfang (Frontiers in Plant Science, 2022)
Predicting the potential influences of climate change on the richness and distribution is essential for the protection of endangered species. Most orchid species are narrowly distributed in specific habitats and they are very vulnerable to habitat disturbance, especially for endangered orchid species on the Qinghai-Tibetan Plateau (QTP). In this study, we simulated the potential influences of climate change on richness and distribution of 17 endangered orchid species on the QTP using MaxEnt model based on the shared socio-economic pathways scenarios (SSPs) in 2050s and 2070s. The results showed that aspect, annual precipitation, elevation, mean temperature of driest quarter, topsoil pH (H2O) and topsoil sand fraction had a large influence on the potential distribution of endangered orchid species on the QTP. The area of potential distribution for orchid species richness ranging from 6 to 11 under current climate scenario was 14,462 km2 (account for 0.56% of QTP), and mostly distributed in the southeastern of QTP. The area of orchid species richness ranging from 6 to 11 under SSP370 in 2070s was the smallest (9370 km2: only account for 0.36% of QTP). The largest area of potential distribution for orchid species richness ranging from 6 to 11 was 45,394 km2 (account for 1.77% of QTP) under SSP585 in 2070s. The total potential distribution area of 17 orchid species richness all increased from 2050s to 2070s under SSP126, SSP245, SSP370 and SSP585 respectively. The orchid species richness basically declined with the increasing elevation under current and future climate scenarios. The mean elevation of potential distribution for orchid species richness ranging from 6 to 11 under different climate scenario was between 3267 m and 3463 m. The mean elevation of potential distribution for orchid species richness ranging from 6 to 11 decreased from SSP126 (3457 m) to SSP585 (3267 m) in 2070s. Based on these findings, future conservation plans should concentrate on the selection of protected areas in the southeastern of QTP to protect the endangered orchid species.